Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

Statement on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - The English Speaking Catholic Council (ESCC) (2021)

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.

[Carter Statement] - The English Speaking Catholic Council (ESCC) (2015)

Submitted to the Select Committee on Dying with Dignity - The English Speaking Catholic Council (ESCC) (2010)
In 1980, a group of individuals who represented various sectors of the English-speaking Catholic community and its organizations met with the idea of consolidating our human and material resources for the development of our community. This led to the formation in 1981 of the English Speaking Catholic Council (ESCC) with a mandate to act as a focal point in coordinating the English-speaking Catholic community of Greater Montreal. Over the years, the ESCC has assumed a higher profile which now extends throughout the Province and beyond. Inspired by the contemporary Catholic understanding of the role of the laity in the modern world, the English Speaking Catholic Council assists in the promotion of its community’s values and advocates those values in the resolution of issues affecting this community. The Board of Directors is made up of women and men from both the private and public sectors, all volunteers, who come together with a commitment to support their community in education, health and social services, community animation, culture and social justice.

Soumis au Comité spécial Mourir avec Dignité par Le conseil catholique d’expression anglaise - The English Speaking Catholic Council (ESCC) (2010)
En 1980, nous, un group d’individus représentant divers secteurs de la communauté Catholique anglophone et ses organisations, nous sommes réunis dans le but de consolider nos ressources humaines et matérielles, en vue du développement de notre communauté. Cela a mené, en 1981, à la création du Conseil catholique d’expression anglaise (CCEA), ayant le mandat d’agir comme point central dans la coordination de la communauté Catholique anglophone de la région urbaine de Montréal. Au cours des ans, l’CCEA a assumé un rôle plus proéminant, élargissant son activité à toute la province et au-delà. S’inspirant de la compréhension Catholique contemporaine du rôle de la communauté laïque dans le monde moderne, Le conseil catholique d’expression anglaise aide à promouvoir les valeurs de sa communauté, et défend ces valeurs dans le processus de résolution des problèmes ayant un impact sur cette communauté. Le conseil d’administration se compose d’hommes et de femmes du secteur public et privé, tous bénévoles, qui s’engagent à appuyer leur communauté dans les domaines de l’éducation, de la santé et des services sociaux, de l’animation sociale, de la culture et de la justice sociale.

Statement on Bill 21 : An Act Respecting the Laicity of the State - The English Speaking Catholic Council (ESCC) (2009)
The English Speaking Catholic Council (ESCC) was founded in 1981 with the mission to act as a catalyst, convener and facilitator of collective action for the English-speaking Catholic community of Quebec. As an organization inspired by Catholic social teaching, the Council is concerned for the common good and is apprehensive as to the implications of Bill 21 (An Act respecting the laicity of the State) for the social and civic welfare of Quebec society. In the main, the objections the Council have regarding the current legislation are similar to those we expressed in our 2013 brief on Bill 60 (Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests)1 However, there are a number of critical differences between the 2013 legislation and that introduced in 2019.

Déclaration sur le projet de loi 21 : Loi sur la laïcité de l’État - The English Speaking Catholic Council (ESCC) (2009)
Le Conseil catholique d’expression anglaise a été fondé en 1981 avec la mission d'agir comme catalyseur, rassembleur et facilitateur de l'action collective pour la communauté catholique anglophone au Québec. En tant qu'organisme inspiré par l'enseignement social catholique, le Conseil se préoccupe du bien commun et s’inquiète donc des implications du projet de loi 21 (Loi sur la laïcité de l'État) pour le bien-être social et civique de la société québécoise. Pour l’essentiel, les objections du Conseil à l'égard de la législation actuelle sont semblables à celles que nous avons exprimées dans notre mémoire de 2013 sur le projet de loi 60 (Charte affirmant les valeurs de la laïcité d'État, de la neutralité religieuse et de l'égalité entre les femmes et les hommes, et fournissant un cadre pour les demandes d'accommodement).

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.